2006
DOI: 10.1002/mrd.20529
|View full text |Cite
|
Sign up to set email alerts
|

Protein gene product 9.5 is a spermatogonia‐specific marker in the pig testis: Application to enrichment and culture of porcine spermatogonia

Abstract: Identification and isolation of spermatogonial stem cells (SSCs) are a prerequisite for culture, genetic manipulation, and/or transplantation research. In this study, we established that expression of PGP 9.5 is a spermatogonia-specific marker in porcine testes. The expression pattern of PGP 9.5 in spermatogonia was compared to cell type-specific protein (GATA-4 or PLZF) expression in seminiferous tubules at different ages, and expression levels of PGP 9.5, Vasa, and Oct-4 were compared in different cell fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
136
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(144 citation statements)
references
References 46 publications
8
136
0
Order By: Relevance
“…The cytoplasmic bridge formed between spermatogonia during colony formation (arrow, b, c) PGP 9.5 positive cells per tubule section) including those were identified as As, Ap and some Aal by morphology [14,25]. Luo et al (2006) established an enrichment method for spermatogonial cells using PGP9.5 marker. Enriched cells containing SSCs were maintained in culture for 2 weeks without losing their PGP9.5 expression [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytoplasmic bridge formed between spermatogonia during colony formation (arrow, b, c) PGP 9.5 positive cells per tubule section) including those were identified as As, Ap and some Aal by morphology [14,25]. Luo et al (2006) established an enrichment method for spermatogonial cells using PGP9.5 marker. Enriched cells containing SSCs were maintained in culture for 2 weeks without losing their PGP9.5 expression [26].…”
Section: Discussionmentioning
confidence: 99%
“…Luo et al (2006) established an enrichment method for spermatogonial cells using PGP9.5 marker. Enriched cells containing SSCs were maintained in culture for 2 weeks without losing their PGP9.5 expression [26]. However, the successfully isolated SSCs in minipigs could not be maintained in culture for more than 10 days [27].…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR analysis demonstrated that UCHL1, PLZF and NANOG, which characterized undifferentiated spermatogonia in pigs [6,23], were expressed in fresh testicular cells and cultured MGSCs (Fig. 5).…”
Section: Rt-pcr Analysis Of Mgscsmentioning
confidence: 99%
“…Markers for undifferentiated spermatogonia from piglets, UCHL1, PLZF [23] and THY1 [20], were expressed in the colonies. VASA, a marker of differentiating spermatogonia [22], was also expressed in the colonies (Fig.…”
Section: Immunocytochemical Analysis Of Cultured Mgscsmentioning
confidence: 99%
“…The resulting cell suspension was immediately submitted to fluorescence-activated cell sorting (FACS) using an in Flux cell sorter (BD Bioscience, San Jose, CA, USA, www.bdbiosciences.com). In some cases, the testicular cell suspension was also submitted to a differential plating method (Luo et al 2006) before FACS. Using this method, somatic cells adhere to the bottom of the plate while germ cells either remain in suspension after 2-3 days of culture or are only loosely associated with the firmly adhering somatic cells (Fig.…”
Section: Expression Of Cyp17a1 and Cyp19a1 Genes In Sorted Testicularmentioning
confidence: 99%